Minimizing Violence: A Good Practice Local Elite-Based in the Madura Island, Indonesia - Daulay, Pardamean; Raditya, Ardhie; Afni Khafsoh, Nur (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2022)
The success of democracy in a nation is measured by the existence of a peaceful, civilised social life. In Indonesia, however, ornaments of violence are still present while resolving issues, as in Madura. This study tries to outline the underlying factors that lead to the formation of violence and pinpoint the function that local elites play in curbing the use of violence. The Galtung theory of violence is utilised in the investigational analysis. In order to analyse the data for this study, we used qualitative research, a case study procedure, and an integration strategy. The findings demonstrated that violence has permeated the Madurese culture. Internally passed down and socially sanctioned, it has been used to cope with a variety of life concerns, such as issues involving wives or women, misunderstandings, inheritance, land, religion or belief, theft, and debts and receivables. Because they have historically served as a point of reference in times of conflict, local elites such as Bhuppa/Bhâbu, Ghuru, Rato (parents, Kiai or the leader in the Islamic religion/teacher, and government) are crucial to the realisation of a culture of non-violence. The local elite’s necessary development of their function does not restrict but rather dampens and empowers, notably among the Bâjing.